The Effect of Teacher Activator Education Program on Pancasila-Based IPAS Learning Implementation at Elementary School - Nurul Kusumaningrum Nurul; E. Kus Eddy Sartono (Universitas Pendidikan Ganesha, 2026)
This study is motivated by the limited integration of strengthening the Profil Pelajar Pancasila character within Science (IPA) learning. It aims to analyze the effect of the Teacher Driving Education Program through the Appreciative Inquiry BAGJA approach on strengthening the Profil Pelajar Pancasila and science learning outcomes. The study employs a quantitative approach with a quasi-experimental design using a pretest–posttest control group design, involving primary school students divided into experimental and control groups. Data were collected using a Likert-scale questionnaire to measure the dimensions of the Profil Pelajar Pancasila and a science achievement test, and were analyzed using an independent samples t-test. The results indicate that the BAGJA approach is significantly more effective than conventional learning in improving science learning outcomes and strengthening the Profil Pelajar Pancasila, demonstrating a strong intervention effect in the experimental group. Therefore, the BAGJA approach can serve as a strategic alternative in developing science learning that not only enhances academic achievement but also reinforces students’ character development in primary education.